A duke for the wallflower's revenge - Dubose, Casey (Harlequin historicals., 2023)
Miss Eliza Hawkins decides to include Gabriel, Duke of Vane, in her plans for revenge on a certain aristocrat at his next house party, but Eliza finds her biggest challenge to be resisting Gabriel's charm.